Fetal growth standards for Chinese twin pregnancies - Jianping Chen; Jun Zhang; Yang Liu; Xing Wei; Yingjun Yang; Gang Zou; Yun Zhang; Tao Duan; Luming Sun (BMC Pregnancy and Childbirth, 2021)
Abstract Background The common use of singleton fetal growth standard to access twin growth might lead to over-monitoring and treatment. We aimed to develop fetal growth standards for Chinese twins based on ultrasound measurements, and compare it with Zhang’s and other twin fetal growth charts. Methods A cohort of uncomplicated twin pregnancies were prospectively followed in 2014–2017. Smoothed estimates of fetal growth percentiles for both monochorionic (MC) and dichorionic (DC) twins were obtained using a linear mixed model. We also created growth charts for twins using a model-based approach proposed by Zhang et al. Our twin standards were compared with Hadlock’s (singleton) in predicting adverse perinatal outcomes. Results A total of 398 twin pregnancies were included, with 214 MC and 582 DC live-born twins. The MC twins were slightly lighter than the DC twins, with small differences throughout the gestation. Our ultrasound-based fetal weight standards were comparable to that using Zhang’s method. Compared with previous references/standards from the US, Brazil, Italy and UK, our twins had very similar 50th percentiles, but narrower ranges between the 5th and 95th or 10th and 90th percentiles. Compared with the Hadlock’s standard, the risks of neonatal death and adverse perinatal outcomes for small for gestational age (SGA) versus non-SGA were substantially elevated using our standards. Conclusions A normal fetal growth standard for Chinese twins was created. The differences between MC and DC twins were clinically insignificant. The 50th weight percentiles of the Chinese twins were identical to those in other races/ethnicities but the ranges were markedly narrower. Our standard performed much better than the Hadlock’s in predicting low birth weight infants associated with adverse perinatal outcomes in twin pregnancies. The present study also indicated that Zhang’s method is applicable to Chinese twins, and other areas may use Zhang’s method to generate their own curves for twins if deemed necessary.